Problems of long-term data storage - Manko, D.Yu.; Beliak, Ie.V.; Morozov, Ye.M. (Реєстрація, зберігання і обробка даних, 2017)
This paper is devoted to analysis of problems of long-term information storage. A short historical overview of the methods of long-term information storage is presented. The overview briefly covers a period from ancient times up to nowadays. The fundamental problems faced by both researchers and private companies working in the field of long-term data storage are highlighted. The main problems come along this long-term data storage, known as digital dark ages are shown. Different ways of overcoming them are revealed. It is shown that many scientific facilities successfully resolved the task of data corruption due to degradation over time and external influence. It is noted that the Institute for information recording, NAS of Ukraine is a research facility proposed and realized a way of overcoming the longevity of data carrier problem. The analysis of the principles of the work of «fast» memory is made, its variants are presented. The possibility of introducing the principles of «fast» visual memory on optical media is considered and discussed. Роботу присвячено аналізу проблем довготермінового зберігання інформації. Представлено короткий історичний огляд методів довготермінового зберігання інформації. Висвітлено фундамен-тальні проблеми, з якими стикаються як дослідники, так і приватні компанії, які працюють в області довготермінового зберігання даних. Показано шляхи подолання існуючих проблем довготермі-нового зберігання. Зроблено аналіз принципів роботи «швидкої» візуальної пам’яті, представлено її різновиди. Розглянуто можливість впровадження принципів «швидкої» пам’яті на оптичних носіях інформації. Работа посвящена анализу проблем долговременного хранения информации. Представлен короткий исторический обзор методов долговременного хранения информации. Освещены фундаментальные проблемы, с которыми сталкиваются как исследователи, так и частные компании, работающие в области долговременного хранения данных. Показаны пути преодоления существующих проблем долговременного хранения. Произведен анализ принципов работы «быстрой» визуальной памяти, представлены ее разновидности. Рассмотрена возможность внедрения принципов «быстрой» памяти на оптических носителях информации.